2021
DOI: 10.3171/2020.8.spine201166
|View full text |Cite
|
Sign up to set email alerts
|

Survival, fusion, and hardware failure after surgery for spinal metastatic disease

Abstract: OBJECTIVEDecompression with instrumented fusion is commonly employed for spinal metastatic disease. Arthrodesis is typically sought despite limited knowledge of fusion outcomes, high procedural morbidity, and poor prognosis. This study aimed to describe survival, fusion, and hardware failure after decompression and fusion for spinal metastatic disease.METHODSThe authors retrospectively examined a prospectively collected, single-institution database of adult patients undergoing decompression and instrumented fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Prior studies have found that increasing age, smoking, preoperative radiotherapy, constructs spanning 6, or more levels, and a prior chest wall resection were risk factors for instrumentation failure after spinal surgery for tumor [ 13 - 18 ]. In contrast, in our study those risk factors were increasing SMII, pelvic fixation, and longer survival of more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have found that increasing age, smoking, preoperative radiotherapy, constructs spanning 6, or more levels, and a prior chest wall resection were risk factors for instrumentation failure after spinal surgery for tumor [ 13 - 18 ]. In contrast, in our study those risk factors were increasing SMII, pelvic fixation, and longer survival of more than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to prior studies, our results did not find that preoperative radiotherapy was a risk factor for hardware failure [ 18 ]. While osteoradionecrosis is a conceivable mechanism [ 31 ] for this this reported association [ 32 ], it was derived from a model with 7 covariates but only 3 failure events, creating a high likelihood of a small-sample bias and a model inaccuracy [ 13 ]. Moreover, 38% of patients in study of Pedreira et al [ 18 ] had a preoperative radiotherapy compared with only 6% in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bone quality of the metastatic vertebrae may be hindered by tumour invasion, systemic cancer treatment and poor nutritional status. 98 While the benefit of spinal fusion is robust in preventing hardware failure in degenerative spine surgery, its necessity is still debatable in the setting of spinal metastasis. 97 99 In metastatic patients, evidence suggests a low fusion rate at 1 year, with only 16.1% achieving complete fusion, after the surgery.…”
Section: Surgical Managementmentioning
confidence: 99%
“… 98 While the benefit of spinal fusion is robust in preventing hardware failure in degenerative spine surgery, its necessity is still debatable in the setting of spinal metastasis. 97 99 In metastatic patients, evidence suggests a low fusion rate at 1 year, with only 16.1% achieving complete fusion, after the surgery. 98 The rate of spinal fusion over a longer time period may be difficult to evaluate due to the high mortality rate.…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation